Generative Anthropology and the Sacred - Gans, Eric Lawrence (2021)
Reflection on the sacred has been part of a reformulation of the originary hypothesis that has evolved over time, as I have sought to conceive the first human event in accordance with the spirit of Occam’s Razor. I have attempted to provide a formulation for the sacred as an anthropological category not governed by the exemplarity of the Crucifixion that motivated Girard to define the sacred as the paradoxical equivalent of violence: la violence ou le sacré.